#### Answer

{$-\frac{1}{2}, 6$}

#### Work Step by Step

$(x-6)(2x+1)=0$
$(x-6)=0$ and $(2x+1)=0$
$(x-6)=0$ and $2x=-1$
$x=6$ and $x=-\frac{1}{2}$
Therefore, the solution set is {$-\frac{1}{2}, 6$}.

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

{$-\frac{1}{2}, 6$}

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.